2012
DOI: 10.1103/physrevlett.108.081803
|View full text |Cite
|
Sign up to set email alerts
|

Puzzle of Anomalously Large Isospin Violations inη(1405/1475)3π

Abstract: The BES-III Collaboration recently reported the observation of anomalously large isospin violations in J/ψ→γη(1405/1475)→γπ(0)f(0)(980)→γ+3π, where the f(0)(980) in the ππ invariant mass spectrum appears to be much narrower (~10 MeV) than the peak width (~50 MeV) measured in other processes. We show that a mechanism, named as triangle singularity (TS), can produce a narrow enhancement between the charged and neutral KK¯ thresholds, i.e., 2m(K(±))~2m(K(0)). It can also lead to different invariant mass spectra f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
166
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(175 citation statements)
references
References 14 publications
9
166
0
Order By: Relevance
“…Another interesting observation is that the width of f 0 (980) is just about 10 MeV which is much narrower than that of about 40 ∼ 100 MeV observed in other processes [11]. These unusual results inspired the study of the isospin violation mechanism for η(1405) → 3π where the ATS mechanism was identified and found to play a key role in accounting for the anomalously large isospin violation effects [12]. In a followed up analysis [13] a mixture of f 1 (1420) was found in J/ψ → γ3π apart from the dominant η(1405) contribution.…”
Section: Anomalous Triangle Singularitymentioning
confidence: 89%
See 2 more Smart Citations
“…Another interesting observation is that the width of f 0 (980) is just about 10 MeV which is much narrower than that of about 40 ∼ 100 MeV observed in other processes [11]. These unusual results inspired the study of the isospin violation mechanism for η(1405) → 3π where the ATS mechanism was identified and found to play a key role in accounting for the anomalously large isospin violation effects [12]. In a followed up analysis [13] a mixture of f 1 (1420) was found in J/ψ → γ3π apart from the dominant η(1405) contribution.…”
Section: Anomalous Triangle Singularitymentioning
confidence: 89%
“…[12,13] that the processes η(1405)/η(1475) and f 1 (1420) decaying into 3π are ideal places to recognize the ATS condition. The intermediate KK * + c.c.…”
Section: Anomalous Triangle Singularitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the f 0 (980) width was found to be 9.5 ± 1.1 MeV/c 2 . One proposed explanation for this anomalously narrow width and the observed large isospin violation, which cannot be caused by a 0 0 (980) − f 0 (980) mixing, is the triangle singularity mechanism [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the results of the first experiments on its discovery in the reactions [30], (e) J/ψ → φf 0 (980)π 0 → φ 3π [31], (f) J/ψ → φf 1 (1285) → φf 0 (980)π 0 → φ 3π [31] have been obtained with the help of detectors VES in Protvino [27,28] and BESIII in Beijing [29][30][31]. The theoretical considerations concerning the BESIII data [30] * achasov@math.nsc.ru † kozhev@math.nsc.ru ‡ shestako@math.nsc.ru on the reaction (d), that is, on the decay η(1405) → f 0 (980)π 0 → 3π, were presented in [32][33][34][35]. Interest in the a 0 0 (980) − f 0 (980) mixing is primarily due to the fact that the amplitude of the isospin breaking transition a 0 0 (980) → (K + K − + K 0K 0 ) → f 0 (980), caused by the mass difference of the K + K − and K 0K 0 intermediate states, in the region between KK thresholds turns out to be of the order of (m K 0 − m K + )/m K 0 [1] [i.e.…”
Section: Introductionmentioning
confidence: 99%